Nasal Reconstruction With Two Stages Versus Three Stages Forehead Fap: What is Better for Patients With High Vascular Risk?. Issue 1 (January 2020) - Lo Torto, Federico; Redi, Ugo; Cigna, Emanuele; Losco, Luigi; Marcasciano, Marco; Casella, Donato; Ciudad, Pedro; Ribuffo, Diego
Abstract : Abstract: In nasal reconstruction, it is necessary to replace all anatomic layers in order to reinstate correct aesthetics. The most apt donor site to use in order to cover the nose has been recognized as forehead skin. Traditionally 2 phases are required to reconstruct the forehead flap; however, an intermediate third phase was described by Millard which is between transfer of the flap and division of the pedicle. These methods will be compared in this study with regard to both complication rates and aesthetic results in high vascular risk patients. 46 patients were enrolled in the study, all of whom were undergoing either total or subtotal nasal reconstruction from January 2001 to March 2018. The 2-step technique (2S Group) was performed on 30 patients and the 3-step technique (3S Group) was performed on 16. Evaluation questionnaires were completed by patients and a plastic surgeon who was extraneous to the study to evaluate aesthetic satisfaction. Complications other than flap necrosis such as infection, wound dehiscence and hematoma were recorded. VAS and Likert mean values, used to evaluate aesthetic satisfaction, were examined with a Student t test and were discovered to be relevant. Complication rates studied with Fisher exact test showed no statistically significant difference between the 2 groups. The 3-phase method for nose reconstruction using a forehead flap represents a better functional and aesthetic option for patients at high vascular risk. Abstract : Supplemental Digital Content is available in the text